EFFECT OF BIO-FERTILIZERS AND NITROGEN MANAGEMENT ON YIELD AND SOIL FERTILITY OF PEARL MILLET UNDER RAINFED CONDITION - CHATRA RAM,; N. I. PATEL,; R. N. SINGH,; K. G. VYAS, (The Bioscan, 2015)
A field experiment was conducted at A1CRPDA Centre, S.D. Agricultural University, Sardarkrushinagar to find out the effect of integrated nutrient management practices in pearl millet crop under rainfed condition. The results showed that the effect of bio-fertilizers were not found significant in increasing the yield as well as soil available nutrients after harvest of the crop during all the years and on pooled basis. The treatment 50% N through urea + 50% N through FYM gave significantly higher seed yield of 1239, 822, 868, 972 and 975 kg ha- 1 during years 2009, 2010, 2011, 2012 as well as in pooled, respectively. The similar trend was also observed in fodder yield. In terms of soil available nitrogen, phosphorus and potash, the treatment 50% N through urea + 50% N through FYM obtained significant improvement in soil fertility status of available N (174 kg/ha), phosphorus (48 kg/ha) and potash (204.8 kg/ha).